Successful Control of Massive Bleeding in a Child with Burkitt’s Lymphoma via a Biosimilar Recombinant Activated Factor VII (AryoSeven™) - Kourosh Goudarzi Pour; Fatemeh Malek; Peyman Eshghi (Case Reports in Hematology)
We describe a case of a 4-year-old girl with Burkitt’s lymphoma, who suffered from a massive gastrointestinal hemorrhage 3 days after chemotherapy. In spite of applying the common practice in correction of coagulopathy, thrombocytopenia persisted and bleeding became life-threatening. In the present case report, we report a successful control of bleeding with a single-dose administration of a biosimilar recombinant activated human factor VII (AryoSeven).